2004
DOI: 10.1038/sj.ejcn.1602034
|View full text |Cite
|
Sign up to set email alerts
|

Immunoenhanced enteral nutrition, effect on inflammatory markers in head and neck cancer patients

Abstract: The aim of our study was to evaluate the effect of enteral nutrition supplemented with arginine in inflammatory markers in surgical head and neck cancer patients. A population of 29 patients with oral and laryngeal cancer were enrolled in a randomized trial. At surgery patients were randomly allocated to two groups: (a) patients receiving an enteral diet supplements with arginine (group I, n ¼ 14); (b) patients receiving an isocaloric, isonitrogenous enteral formula (group II, n ¼ 15). The mean age was 61.1710… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…This finding is in accordance to results of another study showing that IL-6 and IL-1RII were higher in the control group than in the IE group (31). In adult postsurgery patients, however, enhanced formula did not change IL6 and TNF-␣ levels (32). Similarly, low-fat feeding, with or without fish oil, did not change the early production of IL-6 after burn injury (33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in accordance to results of another study showing that IL-6 and IL-1RII were higher in the control group than in the IE group (31). In adult postsurgery patients, however, enhanced formula did not change IL6 and TNF-␣ levels (32). Similarly, low-fat feeding, with or without fish oil, did not change the early production of IL-6 after burn injury (33).…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, it was shown that an enteral formula containing glutamine and probiotics decreased the infection rate and shortened the stay in the intensive care unit of patients with brain injury (38). In another study, also in patients with severe trauma who were fed IE formula, no significant difference was found for mortality and hospital stay (32). The only two well-controlled trials (39,40) also had radically different outcomes, one positive and the other negative, for reductions in infectious complications.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, immunotherapy could be of great value to restrict this mechanism, which could be accomplished by arginase blocking therapy or arginine administration and thereby improve arginine balance (10,35). However, no significant difference in the inflammatory response (lymphocytes, tumor necrosis factor-a, interleukin-6, and C-reactive protein concentrations) was observed in patients with head and neck cancer between an arginine-supplemented group and a control group (36).…”
Section: Discussionmentioning
confidence: 96%
“…Post-surgery enteral nutrition enriched with arginine has been used in most studies [21,22,23,24,25,26] on the basis of its role in wound healing and immune function [27,28] and has been shown to confer beneficial immune effects when provided postoperatively to patients undergoing major surgery for cancer [29]. In head and neck surgery patients the potential beneficial effects of arginine administration on inflammatory and immune markers assessed from POD5 and beyond was not generally evident [21,22,23,24] except in one study [26] that showed improved lymphocyte counts and CD4/CD8 ratios on PODs 4 and 8 in the arginine group compared to control patients. Reduced wound complications [21,23] and postoperative length of stay [23] were reported with arginine administration.…”
Section: Discussionmentioning
confidence: 99%